Pathogenesis and the emerging Therapy of Vitiligo - Zar, Abdur Rahim; Malik, Abdul; Mahmood, Asif; Naseer, Qais Ahmad; Yumei, Li (Archives of Clinical and Biomedical Research, 2019)
Vitiligo is a common and a disfiguring autoimmune disease, which has a negative impact on patients' self-esteem and quality of life. Pathogenesis of Vitiligo involves the interaction between defects of natural and extrinsic melanocytes, immune innate to swelling and destruction of T-cell-mediated melanocyte. Vitiligo affects about 1% of the general population. The risk of the disease was 6% for siblings and 23% for identical twins treatment is not only intended to stop the disease, but also to support repigmentation through the regeneration, proliferation and migration of melanocytes. Treatment strategies for dealing with all aspects of pathogenesis and pigmentation can be very effective, and this strategy may require a combination. Current treatments generally do not imply objective autoimmunity, and emerging treatments may use more specific methods based on a deep understanding of the pathogenesis of the disease, which can provide a good safety profile with a higher effectiveness. However, as with most medical treatments, careful patient selection and monitoring should enable us to normalize the pathogenic response of vitiligo in order to achieve the internal balance of healthy individuals.